PEMBERDAYAAN ORANG TUA MELALUI TEKNIK PIJAT BAYI DENGAN AROMATERAPI PEPPERMINT UNTUK MENGURANGI GEJALA ISPA PADA BALITA - Siregar, Khairani; Savitri, Meili; Sari, Fatimah (Cattleya Darmaya Fortuna, 2025)
Nausea and vomiting (emesis gravidarum) are common complaints experienced by pregnant women, especially during the first trimester. If left untreated, this condition can progress to hyperemesis gravidarum, which poses serious risks to both the mother and the fetus. This activity aimed to provide education and intervention through the use of ginger essential oil in roll-on form as an effort to reduce the frequency of nausea and vomiting in pregnant women. The method of implementation included socialization and presentation of educational materials. Education combined with the use of ginger essential oil in roll-on form proved effective in reducing the frequency of nausea and vomiting. This therapy can serve as a safe, practical, and well-accepted non-pharmacological alternative for pregnant women.